Exploring social media use and its impact on knowledge and behavior during Covid-19 in China - Niu, Panqiang; Li, Ting; Tu, Caixie; Masduki, Anang (Association for Scientific Computing Electrical and Engineering (ASCEE), 2025)
In An extended Cognitive Mediation Model (CMM) was constructed to examine the public's knowledge acquisition and preventive behavioral intentions during the COVID-19 pandemic in the context of social media in China. This extended CMM incorporated three additional variables compared with the original CMM: risk perception, interpersonal communication, and behavioral intention. The motivations for social media use, including surveillance gratification, guidance, anticipated interaction, and risk perception, were positively associated with social media attention, elaboration, and interpersonal communication. Elaboration and interpersonal communication were positively associated with factual and structural knowledge acquisition, which in turn positively influenced behavioral intention. Differential mediation effects were observed: significant indirect effects from motivations to factual knowledge involved elaboration and the combination of attention and elaboration, while all mediation effects from motivations to structural knowledge were significant. Furthermore, mediation paths from motivations to behavioral intention were primarily significant when involving elaboration and structural knowledge, but not factual knowledge. Theoretical and practical implications are discussed.